2021
DOI: 10.1108/jstpm-03-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

Organizational learning, entrepreneurial orientation and personal values towards SMEs’ growth in Indonesia

Abstract: Purpose The purpose of this study is to examine the dimensions of organizational learning (OL), entrepreneurial orientation (EO), personal value toward the firm performance of small and medium enterprises (SMEs) in North Sumatera, Indonesia. Design/methodology/approach This study used a quantitative methodology using Smart partial least squares of the structural equation model. A survey is done by distributing the questionnaires to the respondents (owner-managers) of SMEs across sectors. Using a convenient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 227 publications
(342 reference statements)
1
12
0
5
Order By: Relevance
“…Liu (2020) states that managers should build a learning mechanism to encourage and develop EO. Furthermore, several studies found a relationship between the organizational learning process and EO (Altinay et al, 2016;Bell et al, 2002;Hakala and Kohtamäki, 2011;Rafiki et al, 2021). LO includes a set of values that influence a firm's propensity to proactively seek new knowledge (Slater and Narver, 1995;Sinkula et al, 1997), as well as a learning climate that will undoubtedly contribute to the development of the innovation process and enhance EO (Kumar et al, 2020;Sheng and Chien, 2016).…”
Section: Building Competitive Advantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu (2020) states that managers should build a learning mechanism to encourage and develop EO. Furthermore, several studies found a relationship between the organizational learning process and EO (Altinay et al, 2016;Bell et al, 2002;Hakala and Kohtamäki, 2011;Rafiki et al, 2021). LO includes a set of values that influence a firm's propensity to proactively seek new knowledge (Slater and Narver, 1995;Sinkula et al, 1997), as well as a learning climate that will undoubtedly contribute to the development of the innovation process and enhance EO (Kumar et al, 2020;Sheng and Chien, 2016).…”
Section: Building Competitive Advantagesmentioning
confidence: 99%
“…These firms have been identified as the driving force of economic growth and job creation (Pratono and Mahmood, 2015). It is known that such firms have become a key component of the growth of many economies and play an important role in eliminating poverty, alleviating unemployment and reducing wealth inequality (Rafiki et al , 2021). This is especially true for the Portuguese economy.…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to the entrepreneurial orientation that has been highlighted by many studies. In fact, both PEB and entrepreneurial orientation play a vital role in affecting business performance (Rafiki et al , 2021). The practical implications of research may be beneficial to business owners or entrepreneurs in the decision-making process toward business success.…”
Section: Discussionmentioning
confidence: 99%
“…This paper, therefore, responds to prior calls (Mantok et al, 2019;Rafiki et al, 2023;Rezaei and Fanak, 2019) to explore the OL-EO relationship in NTBFs. Specifically, EO is defined as: "intentions and actions of key players functioning in a dynamic generative process aimed at new-venture creations" (Lumpkin and Dess, 1996, pp.…”
Section: Introductionmentioning
confidence: 92%
“…Entrepreneurial culture and organizational learning in new technology-based firms OL affects performance (Ratnapalan and Uleryk, 2014), and a firm's survival and success against competitors (Rafiki et al, 2023), and are not effective without an appropriate organizational culture (Alsabbagh and Al Khalil, 2017). When organizational culture is shaded by EO, OL is becoming imperative, which ultimately enhances it (Keiser, 2011).…”
Section: Theory and Hypothesesmentioning
confidence: 99%